Monolithic bodies comprising metal-organic frameworks
By integrating water-insoluble and water-soluble polymer binders with MOF, a MOF unitary body with high crush strength is formed, which solves the problem of maintaining the fine structure and properties of MOF and achieves efficient adsorption performance in industrial applications.
Patent Information
- Application Number
- CN202380037934.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-04
- Filing Date
- 2023-05-04
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art is difficult to effectively integrate metal organic frameworks (MOFs) in industrial applications to maintain their fine network structure and properties, especially for industrial applications in adsorption/desorption of molecules or ions.
Using a polymer binder containing a water-insoluble first polymer and a water-soluble second polymer, the monolithic host is enhanced by forming a monolithic host with a metal organic frame (MOF). The strength and the properties of MOF are maintained, and the MOF unitary body with high crush strength is prepared by screen printing, extrusion, slurry casting or 3D printing.
It has achieved the formation of a MOF integral body with high crushing strength and good adsorption properties in industrial applications, which can effectively adsorb analytes such as carbon dioxide, methane, etc., and maintain the original properties of MOF. It is suitable for gas storage and air purification applications.
Smart Images

Figure CN119173337A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS Technical Field
[0002] The present disclosure relates to a monolithic body comprising a metal organic framework (MOF) and a polymer binder. Background Art
[0003] Metal-organic frameworks (MOFs) are coordination networks of metal ions and organic ligands and are a class of compounds known for their unique combination of properties, such as high surface area, high porosity, and flexible adsorption / desorption behavior. MOFs can be tailored to adsorb desired types of molecules or ions with high selectivity.
[0004] There is a need to integrate MOFs into suitable hosts for industrial applications, in which the fine network structure and properties of MOFs can be largely maintained. BRIEF DESCRIPTION OF THE DRAWINGS
[0005] The present disclosure may be better understood, and its numerous features and advantages made apparent to those skilled in the art by referencing the accompanying drawings.
[0006] Figure 1 Included are schemes illustrating a method of making the subject matter of the present disclosure according to one embodiment. DETAILED DESCRIPTION
[0007] As used herein, the terms "comprises," "including," "having," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a process, method, article, or apparatus that comprises a list of features is not necessarily limited to only those features but may include other features not expressly listed or inherent to such process, method, article, or apparatus.
[0008] As used herein, unless expressly stated to the contrary, "or" refers to an inclusive or, not an exclusive or. For example, a condition A or B is satisfied by any of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist).
[0009] In addition, "a" or "an" is used to describe elements and components described herein. This is done merely for convenience and to give a general sense of the scope of the invention. The description should be understood to include one, at least one or the singular, as well as the plural, or vice versa, unless it is clearly indicated otherwise.
[0010] The present disclosure relates to a monolithic body comprising a metal organic framework (MOF) and a polymer binder, wherein the polymer binder may comprise a first polymer and a second polymer, the first polymer being water-insoluble, having a solubility in water of no greater than 5 g / L water at 25° C., and the second polymer being water-soluble, having a solubility in water of at least 10 g / L water at 25° C. The amount of the polymer binder may be at least 3 wt % based on the total weight of the MOF and the polymer binder; and the average crush strength of the monolithic body may be at least 10N.
[0011] As used herein, if not otherwise specified, the term "polymer binder" refers to a combination of a first polymer and a second polymer. In one aspect, the first polymer and the second polymer can be at least partially cross-linked to each other.
[0012] The monolithic body can be designed for industrial applications to adsorb / desorb the desired type of molecules or ions. For example, in non-limiting embodiments, the monolithic body can be used to adsorb carbon dioxide or methane, or for storage of hydrogen, water and air purification, or for catalytic applications.
[0013] As used herein, the term "metal organic framework" (MOF) relates to any compound that forms a network of metal ions with coordinated organic ligands.
[0014] The method of forming the monolithic body of the present disclosure may include preparing a green body composition (11) comprising a MOF, forming a green body (12) from the green body composition, and curing the green body (13) to obtain a monolithic body, such as Figure 1 as shown in .
[0015] In embodiments, forming a green body from the green body composition may include screen printing, extrusion, slip casting, or 3D printing.
[0016] The final shape and size of the monolithic body can vary greatly. For example, the monolithic body can be in the shape of a pellet, or a tube, or a sheet, or can have a spherical shape. In another aspect, the monolithic body can have an irregular shape.
[0017] The polymer binder may comprise a combination of at least one first polymer (P1) and at least one second polymer (P2). In one aspect, the first polymer may be a water-insoluble polymer having a solubility in water of no more than 5 g / L, or no more than 3 g / L, or no more than 1 g / L, or no more than 0.5 g / L at 25°C. In contrast to the first polymer, the second polymer may be a water-soluble polymer having a solubility in water of at least 10 g / L, or at least 30 g / L, or at least 50 g / L, or at least 100 g / L at 25°C. As used herein, if not otherwise specified, the term "first polymer" (P1) refers to the above-mentioned water-insoluble polymer, and the term "second polymer" (P2) refers to the above-mentioned water-soluble polymer.
[0018] In one embodiment, the first polymer may include functional groups that can react with functional groups of the second polymer by forming covalent bonds (also referred to herein as crosslinks).
[0019] In one aspect, the non-limiting example of the functional group of the first polymer can be an amine group, a hydroxyl group, an acrylate group, a vinyl group, a thiol group, a carboxyl group or an epoxy group. In another aspect, the non-limiting example of the functional group of the second polymer can also be an amine group, a hydroxyl group, an acrylate group, a vinyl group, a thiol group, a carboxyl group or an epoxy group, as long as the functional group is different between the first polymer and the second polymer to allow the cross-linking reaction between the functional groups. For example, the first polymer can include an amine group and the second polymer can include a carboxyl group, which can react together to form an amide group, thereby cross-linking the first polymer and the second polymer. In another aspect, the first polymer can include a hydroxyl group, and the second polymer can include a carboxyl group that can form an ester group together.
[0020] In certain embodiments, the first polymer and the second polymer may react during curing of the green body and may form an at least partially cross-linked polymer.
[0021] In one embodiment, the first polymer (water insoluble polymer) can be a polyacrylate, polystyrene, epoxide polymer, polyurethane, polyester, polyether, polyamide, polyimide, or any combination or copolymer thereof. In a particular aspect, the first polymer can be an emulsion polymer.
[0022] The first polymer may further include grafted substitutions that may introduce additional functional groups. For example, a polyacrylate may include amine substitutions next to the acrylate group, which is referred to herein as an amine functionalized polyacrylate.
[0023] In another embodiment, the second polymer (water-soluble polymer) may be, by way of non-limiting example, a polysaccharide, polyethylene glycol, polyamide, polyvinyl alcohol, or polyacrylate.
[0024] In one aspect, the second polymer can be a polysaccharide. Non-limiting examples of polysaccharides can be cellulose derivatives, starch derivatives, alginates, alginate derivatives, or any combination thereof. In particular aspects, the cellulose derivative can be a salt of carboxymethyl cellulose, such as sodium carboxymethyl cellulose (NaCMC).
[0025] In a particular embodiment, the first polymer can be a polyacrylate comprising amine functional groups and the second polymer can be a salt of carboxymethyl cellulose.
[0026] In embodiments, the weight percent ratio of the first polymer to the second polymer (P1:P2) may be in the range of 1:10 to 10:1, or 1:5 to 5:1, or 1:2 to 4:1, or 1:2 to 2:1, or 1:1 to 1:10, or 1:1 to 1:4, or 1:1 to 4:1, or 2:1 to 5:1.
[0027] Depending on the type of the first polymer and the second polymer of the polymer binder, curing may be performed by heat or light radiation (eg, UV radiation).
[0028] The polymer binder of the monolithic body of the present disclosure may have a structure that is permeable to analytes that can be adsorbed by the MOF contained in the binder matrix. Non-limiting examples of analytes may be water, carbon dioxide, ozone, carbon monoxide, hydrogen, methane, ammonia, nitrogen dioxide, water pollutants, or air pollutants.
[0029] It has been surprisingly observed that green body compositions containing certain combinations of a water-insoluble first polymer and a water-soluble second polymer allow for the inclusion of a large amount of metal organic framework (MOF), allowing for the formation of a monolithic body with good strength which can largely retain the properties of the MOF (MOF powder before use).
[0030] The MOF contained in the monolithic body of the present disclosure is not limited to a specific type of MOF. The selection of MOF may depend on the intended use of the subject of the present disclosure. A non-limiting example of MOF may be a network containing metal or transition metal ions of aluminum, copper, iron, zirconium, zinc or beryllium and an organic ligand (e.g., a monovalent, divalent, trivalent or tetravalent organic ligand). Examples of commercially available MOFs may be: MIL-100, MIL-101, Numat 11, Numat 25, HKUST-1, UIO-66, MOF-0, MOF-2, MOF-3, MOF-4, MOF-5, MOF-6, MOF-7, MOF-8, MOF-9, MOF-11, MOF-12, MOF-20, MOF-25, MOF-26, MOF-31, MOF-32, MOF-33, MOF-34, MOF-36, MOF-37, MO F-38, MOF-39, MOF-47, MOF-49, MOF-69a, MOF-69b, MOF-74, MOF-101, MOF-102, MOF-107, MOF-10 8. MOF-110, MOF-177, MOF-j, MOF-n, IRMOF-1, IRMOF-2, IRMOF-3, IRMOF-4, IRMOF-5, IRMOF-6, I RMOF-7, IRMOF-8, IRMOF-9, IRMOF-10, IRMOF-11, IRMOF-12, IRMOF-13, IRMOF-14, IRMOF-15, IR MOF-16, IRMOF-17, IRMOF-18, IRMOF-19, IRMOF-20, AS16, AS27-2, AS32, AS54-3, AS61-4, AS68- 7. BPR43G2, BPR48A2, BPR49B1, BPR68D10, BPR69B1, BPR73E4, BPR76D5, BPR80D5, BPR92A2, BPR9 5C5, UiO-67, UiO-68, NO13, NO29, NO305, NO306A, NO330, NO332, NO333, NO335, NO336 or HKUST-1.
[0031] In one embodiment, the metal organic framework may include an average particle size of at least 0.020 μm, such as at least 0.050 μm, or at least 0.1 μm, or at least 0.2 μm, or at least 0.5 μm, or at least 1 μm, or at least 3 μm, or at least 5 μm, or at least 8 μm, or at least 10 μm. In another aspect, the average particle size of the MOF may be no greater than 1000 μm, or no greater than 800 μm, or no greater than 500 μm, or no greater than 300 μm, or no greater than 200 μm, or no greater than 100 μm, or no greater than 50 μm, or no greater than 10 μm, or no greater than 7 μm, or no greater than 5 μm, or no greater than 1 μm, or no greater than 0.5 μm, or no greater than 0.1 μm. The average particle size of the MOF may be a value between any of the above minimum and maximum values.
[0032] In a certain embodiment, the MOF can be a shaped particle. In one aspect, the shaped particle can have an aspect ratio of length to width greater than 1.0, such as greater than 1.2, or greater than 1.5, or greater than 2.0, or greater than 3.0, or greater than 5.0, or greater than 10.0.
[0033] In one embodiment, the monolithic body may include a majority of the total weight of MOF. In a particular aspect, the weight % ratio of MOF to polymer binder may be no greater than 2:1, or no greater than 5:1, or no greater than 10:1, or no greater than 15:1, or no greater than 20:1, or no greater than 25:1, or no greater than 30:1. In another aspect, the weight % ratio of MOF to polymer binder may be at least 40:1, or at least 35:1, or at least 30:1, or at least 25:1. The weight % ratio of MOF to polymer binder may be a value within a range including any of the above minimum and maximum values, such as 2:1 to 40:1, or 5:1 to 30:1, or 10:1 to 25:1, or 15:1 to 20:1.
[0034] In another aspect, the amount of MOF in the monolithic body can be at least 70 wt %, such as at least 75 wt %, at least 80 wt %, at least 85 wt %, at least 90 wt %, at least 95 wt %, or at least 97 wt %, based on the total weight of the monolithic body. In a further aspect, the amount of MOF in the monolithic body can be no greater than 98 wt %, or no greater than 97 wt %, or no greater than 95 wt %, based on the total weight of the functional layer. The amount of MOF in the monolithic body can be a value within a range including any of the above minimum and maximum values.
[0035] In another embodiment, the amount of polymer binder included in the monolithic body can be at least 1 wt %, or at least 3 wt %, or at least 5 wt %, or at least 8 wt %, or at least 10 wt %, at least 12 wt %, or at least 15 wt %, or at least 18 wt %, or at least 20 wt %, based on the total weight of the polymer binder and the MOF. In another aspect, the amount of the polymer binder can be no more than 30 wt %, such as no more than 25 wt %, no more than 20 wt %, no more than 15 wt %, no more than 10 wt %, or no more than 5 wt %, based on the total weight of the polymer binder and the MOF. In a specific aspect, the amount of the polymer binder can be at least 5 wt % and no more than 15 wt %, based on the total weight of the polymer binder and the MOF. The amount of the polymer binder can be a value between any of the above minimum and maximum values.
[0036] In one embodiment, the monolithic body of the present disclosure may have a normalized functionality ratio (NFR) of at least 0.5. As used herein, the normalized functionality ratio (NFR) is defined as the ratio of a property of the monolithic body to a corresponding property of the MOF prior to inclusion in the monolithic body. In one aspect, the property may be specific surface area (SSA), or adsorption capacity for analytes, or porosity, or pore volume.
[0037] In certain aspects, the NFR can be at least 0.55, or at least 0.60, or at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.92, or at least 0.94, or at least 0.95, or at least 0.96, or at least 0.97, or at least 0.99.
[0038] In another embodiment, the monolithic body may have a specific surface area (SSA) of at least 850 m 2 / g, or at least 900m 2 / g, or at least 950m 2 / g, or at least 1000m 2 / g, or at least 1050m 2 / g, or at least 1100m 2 / g, or at least 1150m 2 / g, or at least 1200m 2 / g, or at least 1250m 2 / g, or at least 1300m 2 / g, or at least 1350m 2 / g, or at least 1400m 2 / g. In another aspect, the SSA of the monolithic body may be no greater than 2500 m 2 / g, or not more than 2000m2 / g, or not more than 1800m 2 / g, or not more than 1500m 2 / g.
[0039] In further embodiments, the monolithic body may have a water adsorption capacity of at least 0.10 g HO / g MOF, or at least 0.15 g HO / g MOF, or at least 0.17 g HO / g MOF, or at least 0.20 g HO / g MOF, or at least 0.25 g HO / g MOF, or at least 0.30 g HO / g MOF at a temperature of 25° C. and a relative humidity of 30%.
[0040] In another embodiment, the monolithic body may have a water adsorption capacity of at least 0.15 g H2O / g MOF, or at least 0.17 g H2O / g MOF, or at least 0.20 g H2O / g MOF, or at least 0.25 g H2O / g MOF, or at least 0.30 g H2O / g MOF at a temperature of 25°C and a relative humidity of 80%.
[0041] In one embodiment, the method of preparing the monolithic body of the present disclosure may include forming a green body composition as a first step. In one aspect, forming the green body composition may include mixing the MOF, a polymer binder (a first polymer and a second polymer), and a solvent, wherein the second polymer is dissolved in the solvent, and the first polymer is not dissolved in the solvent or only a small portion of the first polymer is dissolved in the solvent. In a specific aspect, the first polymer can be an emulsion polymer.
[0042] In one aspect, the weight % ratio of MOF to polymer binder in the composition can be in the range of 2: 1 to 50: 1. In certain aspects, the weight % ratio of MOF to polymer binder can be in the range of 5: 1 to 30: 1, 10: 1 to 25: 1, or 15: 1 to 20: 1.
[0043] In certain embodiments, the solvent of the green body composition may include water. In certain embodiments, the solvent may consist essentially of water, except for unavoidable impurities.
[0044] In a further certain aspect, the green body composition can include one or more optional additives, such as surfactants, dispersants, pH adjusters, buffers, fillers, or viscosity modifiers.
[0045] In a further aspect, the green composition can have a pH between 1 and 12, in particular between 3 and 11. In a particular aspect, the pH is at least 4.5 and not greater than 10, or at least 7 and not greater than 10.
[0046] In one aspect, the amount of MOF in the green body composition can be at least 10 wt%, or at least 15 wt%, or at least 20 wt%, or at least 25 wt%, or at least 30 wt%, or at least 50 wt%, or at least 70 wt%, or at least 80 wt%. In another aspect, the amount of MOF can be no greater than 90 wt%, or no greater than 80 wt%, or no greater than 70 wt%, or no greater than 60 wt%, or no greater than 50 wt%, or no greater than 40 wt%, or no greater than 30 wt%, or no greater than 25 wt%, or no greater than 20 wt%. The amount of MOF in the green body composition can be a value between any of the above minimum and maximum values.
[0047] In a further aspect, the amount of polymer binder in the green body composition can be at least 2 wt%, or at least 5 wt%, or at least 10 wt%, or at least 20 wt%, based on the total weight of the green body composition. In another aspect, the amount of polymer binder in the green body composition can be no more than 50 wt%, or no more than 30 wt%, or no more than 20 wt%, or no more than 10 wt%. The amount of binder in the green body composition can be a value between any of the above minimum and maximum values.
[0048] In yet another aspect, the amount of solvent in the green body composition can be at least 10 wt %, such as at least 20 wt %, or at least 30 wt %, or at least 40 wt %, or at least 50 wt %, or at least 60 wt %, based on the total weight of the green body composition. In another aspect, the amount of solvent can be no more than 80 wt %, or no more than 60 wt %, or no more than 50 wt %, or no more than 30 wt %, based on the total weight of the green body composition. The amount of solvent in the green body composition can be a value between any of the above minimum and maximum values.
[0049] In certain embodiments, the green body composition can be a paste suitable for filling a mold, or passing through a screen, or suitable for extrusion. In one aspect, the paste can be filled in a mold to form a shaped green body, such as a belt with a shaped opening, and the shaped green body can be cured at an elevated temperature to form a monolithic body.
[0050] The temperature for curing the green body may be at least 60°C, or at least 80°C, or at least 100°C, or at least 130°C. In another aspect, the temperature for curing may be no greater than 250°C, or no greater than 200°C, or no greater than 150°C.
[0051] In a particular embodiment, the monolithic body of the present disclosure may be a filter or filter material suitable for filtering gases or fluids by adsorbing specific analytes.
[0052] The monolithic body of the present invention can have good strength. In one embodiment, the average crushing strength of the monolithic body can be at least 5N, or at least 10N, or at least 15N, or at least 20N, or at least 15N, or at least 30N, or at least 35N. In another aspect, the crushing strength can be no more than 150N, or no more than 100N, or no more than 50N, or no more than 40N. The average crushing strength can be a value between any one of the above minimum and maximum values, such as 10N to 100N, or 20N to 50N, or 25N to 45N. As used herein, the crushing strength is determined by testing pellets having a diameter of 1.60mm and a thickness of 0.76mm.
[0053] Many different aspects and embodiments are possible. Some of those aspects and embodiments are described herein. After reading this specification, the technical staff will understand that those aspects and embodiments are only exemplary and do not limit the scope of the present invention. Embodiment can be according to any one or more embodiments in the embodiments listed below.
[0054] Implementation
[0055] Embodiment 1. A monolithic body comprising a metal organic framework (MOF) and a polymer binder, wherein the polymer binder comprises a first polymer and a second polymer, the first polymer is water-insoluble and has a solubility in water of no more than 5 g / L water at 25°C, and the second polymer is water-soluble and has a solubility in water of at least 10 g / L water at 25°C; based on the total weight of the MOF and the polymer binder, the amount of the polymer binder is at least 3 weight %; and the average crush strength of the monolithic body is at least 10N.
[0056] Embodiment 2. A monolithic host according to Embodiment 1, wherein the monolithic host has a normalized functionality ratio (NFR) of at least 0.5, wherein the NFR is a ratio of the properties of the monolithic host to the properties of the MOF prior to inclusion in the monolithic host.
[0057] Embodiment 3. A monolithic body according to Embodiment 2, wherein the property of the NFR is selected from the group consisting of specific surface area (SSA); adsorption capacity for analytes; pore volume; porosity, or a combination thereof.
[0058] Embodiment 4. A monolithic body according to Embodiment 4, wherein the NFR is at least 0.55, or at least 0.6, or at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 0.98.
[0059] Embodiment 5. A monolithic body according to Embodiment 3 or 4, wherein the property of the NFR is specific surface area (SSA).
[0060] Embodiment 6. A monolithic body according to any of the preceding embodiments, wherein the monolithic body has a specific surface area (SSA) of at least 850 m2 / g, or at least 900 m2 / g, or at least 950 m2 / g, or at least 1000 m2 / g, or at least 1050 m2 / g, or at least 1100 m2 / g, or at least 1150 m2 / g, or at least 1200 m2 / g, or at least 1250 m2 / g, or at least 1300 m2 / g, or at least 1350 m2 / g, or at least 1400 m2 / g.
[0061] Embodiment 7. A monolithic body according to any of the preceding embodiments, wherein the specific surface area (SSA) is not greater than 2500 m2 / g, or not greater than 2000 m2 / g, or not greater than 1500 m2 / g.
[0062] Embodiment 8. A monolithic body according to embodiment 3, wherein the analyte comprises at least one of water, carbon dioxide, methane, ammonia, hydrogen, water contaminants, or air contaminants.
[0063] Embodiment 9. A monolithic body according to embodiment 8, wherein the NFR of the adsorption capacity of the analyte is at least 0.6, or at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 0.96, or at least 0.97, or at least 0.98, or at least 0.99.
[0064] Embodiment 10. A monolithic body according to any of the preceding embodiments, wherein the monolithic body comprises a water adsorption capacity of at least 0.10 g H2O / g MOF, or 0.15 g H2O / g MOF, or at least 0.17 g H2O / g MOF, or at least 0.20 g H2O / g MOF, or at least 0.25 g H2O / g MOF, or at least 0.30 g H2O / g MOF at a temperature of 25°C and a relative humidity of 30%.
[0065] Embodiment 11. A monolithic body according to any of the preceding embodiments, wherein the monolithic body comprises a water adsorption capacity of at least 0.15 g HO / g MOF, or at least 0.17 g HO / g MOF, or at least 0.20 g HO / g MOF, or at least 0.25 g HO / g MOF, or at least 0.30 g HO / g MOF at a temperature of 25° C. and a relative humidity of 80%.
[0066] Embodiment 12. A monolithic body according to any of the preceding embodiments, wherein the MOF comprises an average particle size (D50) of at least 0.020 μm, or at least 0.050 μm, or at least 0.1 μm, or at least 0.2 μm, or at least 0.5 μm, or at least 1 μm, or at least 3 μm, or at least 5 μm, or at least 8 μm, or at least 10 μm.
[0067] Embodiment 13. A monolithic body according to any of the preceding embodiments, wherein the MOF comprises an average particle size (D50) of not more than 1000 μm, or not more than 800 μm, or not more than 500 μm, or not more than 300 μm, or not more than 200 μm, or not more than 100 μm, or not more than 50 μm, or not more than 10 μm, or not more than 7 μm, or not more than 5 μm, or not more than 1 μm, or not more than 0.5 μm, or not more than 0.1 μm.
[0068] Embodiment 14. A monolithic body according to any of the preceding embodiments, wherein the MOF may be a shaped MOF particle.
[0069] Embodiment 15. A monolithic body according to Embodiment 14, wherein the shaped MOF particles have an aspect ratio of length to width greater than 1.0.
[0070] Embodiment 16. A monolithic body according to Embodiment 14 or 15, wherein the aspect ratio length to width of the shaped MOF particles is at least 1.1, or at least 1.5, or at least 2.0, or at least 3.0, or at least 5.0, or at least 10.0.
[0071] Embodiment 17. A monolithic body according to any of the preceding embodiments, wherein the MOF comprises aluminum fumarate, or MIL-100, or MIL-101, or Numat-11, or Numat-25, or UIO-66, or a transition metal-based MOF, or MOF-0, MOF-2, MOF-3, MOF-4, MOF-5, MOF-6, MOF-7, MOF-8MOF-9, MOF-11, MOF-12, MOF-20, MOF-25 , MOF-26, MOF-31, MOF-32, MOF-33, MOF-34, MOF-36, MOF-37, MOF-38, MOF-39, MOF-47, MOF-49, MOF-69a, MOF- 69b, MOF-74, MOF-101, MOF-102, MOF-107, MOF-108, MOF-110, MOF-177, MOF-j, MOF-n, IRMOF-1, IRMOF-2, IRMO F-3, IRMOF-4, IRMOF-5, IRMOF-6, IRMOF-7, IRMOF-8, IRMOF-9, IRMOF-10, IRMOF-11, IRMOF-12, IRMOF-13, IR MOF-14, IRMOF-15, IRMOF-16, IRMOF-17, IRMOF-18, IRMOF-19, IRMOF-20, AS16, AS27-2, AS32, AS54-3, AS61-4 , AS68-7, BPR43G2, BPR48A2, BPR49B1, BPR68D10, BPR69B1, BPR73E4, BPR76D5, BPR80D5, BPR92A2, BPR95C5, UiO-67, UiO-68, NO13, NO29, NO305, NO306A, NO330, NO332, NO333, NO335, NO336, HKUST-1, UTSA-16, or any combination thereof.
[0072] Embodiment 18. A monolithic body according to any of the preceding embodiments, wherein the weight % ratio of the MOF to the binder in the monolithic body is at least 5:1, or at least 8:1, or at least 10:1, or at least 15:1, or at least 20:1, or at least 30:1, or at least 40:1, or at least 50:1.
[0073] Embodiment 19. A monolithic body according to any of the preceding embodiments, wherein the weight % ratio of the MOF to the binder in the monolithic body is not greater than 100:1, or not greater than 70:1, or not greater than 50:1, or not greater than 30:1, or not greater than 20:1, or not greater than 15:1, or not greater than 10:1.
[0074] Embodiment 20. A monolithic body according to any of the preceding embodiments, wherein the amount of MOF is at least 70 wt%, or at least 75 wt%, or at least 80 wt%, or at least 85 wt%, or at least 90 wt%, or at least 95 wt%, or at least 98 wt%, based on the total weight of the monolithic body.
[0075] Embodiment 21. A monolithic body according to any of the preceding embodiments, wherein the amount of MOF is not greater than 99.5 wt%, such as not greater than 99 wt%, or not greater than 97 wt%, based on the total weight of the monolithic body.
[0076] Embodiment 22. An integral body according to any of the preceding embodiments, wherein the amount of the adhesive is not greater than 30 weight %, or not greater than 25 weight %, or not greater than 20 weight %, or not greater than 15 weight %, or not greater than 10 weight %, or not greater than 5 weight %, or not greater than 3 weight %, based on the total weight of the integral body.
[0077] Embodiment 23. A monolithic body according to any of the preceding embodiments, wherein the amount of the binder is at least 0.5 wt%, or at least 1 wt%, or at least 3 wt%, or at least 5 wt%, based on the total weight of the monolithic body.
[0078] Embodiment 24. A monolithic body according to any one of the preceding embodiments, wherein the monolithic body is a pellet, a tube, a sheet, has a round shape or has an irregular shape.
[0079] Embodiment 25. A monolithic body according to Embodiment 24, wherein the monolithic body is a pellet.
[0080] Embodiment 26. A monolithic body according to Embodiment 25, wherein the pellets have an aspect ratio of length to thickness of 1:1 to 10:1.
[0081] Embodiment 27. A monolithic body according to Embodiment 24 or 25, wherein the pellets have a thickness of at least 0.1 mm, or at least 0.3 mm, or at least 0.5 mm, or at least 0.8 mm, or at least 1.0 mm, or at least 1.2 mm, or at least 1.4 mm, or at least 1.6 mm, or at least 1.8 mm, or at least 2.0 mm.
[0082] Embodiment 28. A monolithic body according to embodiment 24 or 25, wherein the pellet has a thickness of no greater than 5.0 mm, or no greater than 4.0 mm, or no greater than 3.0 mm, or no greater than 2.0 mm, or no greater than 1.0 mm.
[0083] Embodiment 29. A monolithic body according to any one of Embodiments 24 to 28, wherein the pellets have a length of at least 0.5 mm, or at least 1.0 mm, at least 1.3 mm, or at least 1.5 mm, or at least 2.0 mm, or at least 3 mm, or at least 5 mm.
[0084] Embodiment 30. A monolithic body according to any one of Embodiments 24 to 28, wherein the pellets have a length of no greater than 10 mm, or no greater than 8 mm, or no greater than 5 mm, or no greater than 3.0 mm, or no greater than 2.0 mm.
[0085] Embodiment 31. A monolithic body according to any of the preceding embodiments, wherein the crush strength of the monolithic body is at least 5N, or at least 10N, or at least 15N, or at least 20N, or at least 15N, or at least 30N, or at least 35N.
[0086] Embodiment 32. A monolithic body according to any one of the preceding embodiments, wherein the crush strength of the monolithic body is not greater than 150N, or not greater than 100N, or not greater than 50N, or not greater than 40N.
[0087] Embodiment 33. A monolithic body according to any of the preceding embodiments, wherein the first polymer comprises functional groups and the second polymer comprises functional groups, and the functional groups of the first polymer are capable of forming covalent bonds with the functional groups of the second polymer.
[0088] Embodiment 34. A monolithic body according to Embodiment 33, wherein the functional group of the first polymer is selected from an amine group, a hydroxyl group, an acrylate group, a vinyl group, a thiol group, a carboxyl group or an epoxy group.
[0089] Embodiment 35. A monolithic body according to embodiment 33 or 34, wherein the functional group of the second polymer is selected from carboxyl, hydroxyl, amine, acrylate or vinyl.
[0090] Embodiment 36. A monolithic body according to any of the preceding embodiments, wherein the first polymer comprises at least one polyacrylate, polystyrene, epoxide polymer, polyurethane, polyester, polyether, polyamide, polyimide, or any combination or copolymer thereof.
[0091] Embodiment 37. A monolithic body according to Embodiment 36, wherein the first polymer is an emulsion polymer.
[0092] Embodiment 38. A monolithic body according to Embodiment 36 or 37, wherein the first polymer comprises a polyacrylate comprising amine functional groups.
[0093] Embodiment 39. A monolithic body according to any of the preceding embodiments, wherein the second polymer comprises a polysaccharide, polyethylene glycol, a polyamide, polyvinyl alcohol, or a polyacrylate.
[0094] Embodiment 40. A monolithic body according to embodiment 39, wherein the second polymer comprises a polysaccharide selected from a cellulose derivative or a starch derivative, an alginate or an alginate derivative.
[0095] Embodiment 41. A monolithic body according to Embodiment 40, wherein the polysaccharide comprises a salt of carboxymethyl cellulose.
[0096] Embodiment 42. A monolithic body according to any of the preceding embodiments, wherein the polymer binder comprises at least partially cross-linked polymers of Polymer 1 and Polymer 2.
[0097] Embodiment 43. A monolithic body according to Embodiment 42, wherein the first polymer comprises a polyacrylate comprising amine functional groups, and the second polymer comprises sodium carboxymethyl cellulose, and the polyacrylate comprising amine functional groups is at least partially cross-linked with the sodium carboxymethyl cellulose (NaCMC).
[0098] Embodiment 44. A monolithic body according to any of the preceding embodiments, wherein the weight percentage ratio of polymer 1 to polymer 2 (P1:P2) is in the range of 1:10 to 10:1, or 1:5 to 5:1, or 1:2 to 4:1, or 1:1 to 3:1.
[0099] Embodiment 45. The monolithic body of any of the preceding embodiments, wherein the monolithic body further comprises an inorganic binder.
[0100] Embodiment 46. A monolithic body according to Embodiment 45, wherein the inorganic binder comprises hydroxyl groups.
[0101] Embodiment 47. A monolithic body according to Embodiment 45 or 46, wherein the inorganic binder comprises aluminum hydroxide.
[0102] Embodiment 48. A monolithic body according to Embodiment 47, wherein the inorganic binder comprises boehmite of gibbsite.
[0103] Embodiment 49. A monolithic body according to any one of the preceding embodiments, wherein the monolithic body comprises a first pore structure and a second pore structure, wherein the first pore structure relates to openings of particles of the MOF, and the second pore structure relates to openings formed within the adhesive and between the adhesive and the particles of the MOF.
[0104] Embodiment 50. A monolithic body according to Embodiment 49, wherein the average pore size of the first pore structure is different from the average pore size of the second pore structure.
[0105] Embodiment 51. A monolithic body according to Embodiment 50, wherein the average pore size of the second pore structure is greater than the average pore size of the first pore structure.
[0106] Embodiment 52. A monolithic body according to any of the preceding embodiments, wherein the binder is permeable to an analyte capable of being adsorbed by the MOF.
[0107] Embodiment 53. A monolithic body according to Embodiment 52, wherein the analyte comprises at least one of water, carbon dioxide, hydrogen, methane, ammonia, a water pollutant, or an air pollutant.
[0108] Embodiment 54. A monolithic body according to any of the preceding embodiments, wherein the density of the monolithic body is at least 1.5 g / cm 3 , or at least 1.8g / cm 3 , or at least 2.0g / cm 3 , or at least 2.2g / cm 3 , or at least 2.3g / cm 3 .
[0109] Embodiment 55. A monolithic body according to any one of the preceding embodiments, wherein the density of the monolithic body is not greater than 3.5 g / cm 3 , or not more than 3.0g / cm 3 , or not more than 2.8g / cm 3 , or not more than 2.6g / cm 3 .
[0110] Embodiment 56. A method for preparing a monolithic body comprising a metal organic framework (MOF), the method comprising preparing a green body composition comprising a MOF, a first polymer and a second polymer, wherein the first polymer has a solubility in water of no more than 5 g / L water at 25°C, and the second polymer has a solubility in water of at least 10 g / L water at 25°C; forming a shaped green body from the green body composition; and curing the shaped green body to obtain the monolithic body.
[0111] Embodiment 57. A method according to Embodiment 56, wherein curing comprises heat treatment at a temperature of at least 60°C, or at least 80°C, or at least 100°C, or at least 130°C.
[0112] Embodiment 58. A method according to Embodiment 56, wherein curing comprises heat treatment at a temperature not greater than 350°C, or not greater than 300°C, or not greater than 250°C, or not greater than 200°C, or not greater than 160°C, or not greater than 130°C.
[0113] Embodiment 59. A method according to any one of Embodiments 56 to 58, wherein forming the shaped green body comprises screen printing, extrusion, slip casting, injection molding or 3D printing.
[0114] Embodiment 60. The method of any one of Embodiments 56 to 59, wherein the green composition is a paste.
[0115] Embodiment 61. A method according to Embodiment 60, wherein the paste has a water content of not greater than 50 wt%, or not greater than 40 wt%, or not greater than 30 wt%, or not greater than 25 wt%, based on the total weight of the green composition.
[0116] Embodiment 62. The method of any one of Embodiments 56 to 61, wherein the polymer binder is selected from any one of the polymer binders of Embodiments 33 to 44.
[0117] Example
[0118] The following non-limiting examples illustrate the invention.
[0119] Example 1
[0120] A two-component polymer adhesive system containing a water-insoluble polymer (polymer 1) and a water-soluble polymer (polymer 2) was used with the following polymer combination: as the water-insoluble polymer, an acrylic polymer emulsion Rhoplex GL-618 was used, and sodium carboxymethylcellulose (NaCMC) with a molecular weight of 90,000 g / mol (product 12M8P from Ashland), a water-soluble cellulose derivative.
[0121] First, a paste was prepared by combining: 10 g UTSA-16 type MOF powder, a cobalt citrate type compound suitable for adsorbing CO2, with a D50 particle size of about 5 microns; 2.12 g Rhoplex GL-618 (having a solid content of 47 wt. %); and 2 g NaCMC, a 10 wt. % NaCMC aqueous solution, and kneading the mixture manually for 3 minutes. The paste, also referred to herein as a green body composition, was further subjected to forming a green body in the shape of a pellet via screen printing, followed by curing of the formed green body. The total amount of polymer binder in the cured pellets was about 11 wt. % based on the total weight of the polymer binder and MOF.
[0122] The above screen printing was performed by using a tape made of PEEK having a thickness of 0.76 mm and containing circular through holes having a diameter of 1.6 mm. The through holes of the tape were filled with the paste via a doctor blade. The screen-printed pellets were dried by heating at 100° C. for one hour.
[0123] Crush strength measurement
[0124] The pellets were tested for crushing strength using an MTS Sintech 2 / G system with a load cell sensitivity of 0.01 N. The head of the measuring unit was positioned just in contact with the test pellet and crushing was performed using a constant displacement. The displacement was set to 2 μm / s until the pellet failed. The instrument indicated failure by a sudden drop in load from the maximum load.
[0125] The average crush strength obtained for the above pellets comprising the polymer binder combination of Rhoplex GL618 and NaCMC was 37N.
[0126] A summary of the crush strength test results is shown in Table 1.
[0127] Table 1 :
[0128] sample Adhesives Average crushing strength [N] <![CDATA[Density [g / cm 3 > S1 P1+P2 combination 37 2.0458 S2 Boehmite 21.5 2.552 S3 Arginine salt 13 2.3983
[0129] MOF-containing pellets with boehmite binder
[0130] A paste was formed by combining 5 g of MOF (UTSA-16), 0.68 g of boehmite (P2 Disperal from Sasol) and 3 g of deionized water and kneading the mixture manually for 3 minutes.
[0131] Screen printing was performed in the same manner as the above-mentioned pellets containing a polymer binder, except that heating was performed at 150°C for two hours.
[0132] The results of the crush strength test (Sample S2) are also summarized in Table 1. It can be seen that the pellets formed with the boehmite binder have a lower crush strength than the pellets prepared with the polymer binder combination of Polymer 1 and Polymer 2.
[0133] MOF-containing pellets with alginate binder
[0134] A paste was formed by combining 6.41 g of MOF (UTSA-16, a MOF with a D50 size of about 5 microns for adsorbing CO2) with 3.14 g of ammonium alginate (4 wt% aqueous solution of ammonium alginate) via manual kneading for 3 minutes.
[0135] Screen printing was performed in the same manner as for the pellets containing the polymer binder described above, except that after filling the holes of the tape, the paste in the holes of the tape was exposed to a 30% calcium chloride solution by wiping the surface with a paper towel moistened with the calcium chloride solution. After the calcium chloride treatment (which caused cross-linking of the alginate), heating was performed at 100°C for 15 minutes.
[0136] The crushing strength test results showed that the average crushing strength of the pellets prepared using alginate as a binder was 13N, which was lower than the crushing strength of the pellets containing a polymer binder combination or a boehmite binder.
[0137] Example 2
[0138] A series of MOF-containing pellets were prepared by combining a two-component polymer binder combination of Rhoplex GL-618 (polymer 1) and NaCMC (polymer 2), also used in Example 1, with a MIL-100 (Fe) type metal organic framework powder (from AEOL). MIL-100 (Fe) is an iron (III) based compound with trimesic acid ligands, having a D50 particle size of about 9.4 microns (measured with a Horiba LA-950 laser scattering particle size analyzer). The samples were varied by the total amount of polymer binder (5 wt%, 10 wt%, 15 wt%, and 20 wt% based on the total weight of the MOF and polymer binder) and by varying the ratio of Rhoplex GL-618 (polymer 1) to NaCMC (polymer 2). The weight percentage ratios of polymer 1 to polymer 2 (P1 to P2) were 1.5 to 1.0; 1.0 to 1.0; 1.0 to 1.5; 1.0 to 2.33 and 1 to 4. Each sample was kneaded manually for 3 minutes and, if necessary, a small amount of water was added to form a paste (green composition) and screen printed and cured as described in Example 1.
[0139] The specific surface area (SSA) was measured from the obtained pellets using a Micromeritics TriStar II Plus gas adsorption analyzer according to the BET method. The measurement was performed using nitrogen as the adsorbent.
[0140] In addition, the crush strength (CS) of pellets having polymer ratios of 1.5 to 1.0; and 1.0 to 1.0; and 1.0 to 4.0 were measured in the same manner as described in Example 1 at different total binder concentrations.
[0141] A summary of the SSA values, calculated NFR and crush strength of the pellets is shown in Tables 2, 3 and 4.
[0142] Table 2 :
[0143]
[0144] Table 3 :
[0145]
[0146] Table 4 :
[0147]
[0148] The SSA of the pellets (sample S16) with a P1:P2 ratio of 1:2.33 and a total binder content of 15 wt% is not shown in the above table, and its SSA is 1135 m 2 / g; and for pellets with a P1:P2 ratio of 1:1.5, the SSA is 1296m when the total binder content is 5mg 2 / g (Sample 17), and the SSA of 15 wt% total binder is 1006 m 2 / g(Sample 18).
[0149] From the summarized data, it can be seen that the highest SSA is obtained with a 1: 1 weight percent ratio of Rhoplex to NaCMC (P1 and P2). Very similar SSA values are obtained with a 1.5: 1 binder ratio of P1 to P2, with the advantage of increased crush strength.
[0150] A comparative example was prepared by preparing pellets made with only Rhoplex GL618 (Polymer 1) and Mil-100 (Fe). The pellets containing 32 wt. % Rhoplex (Polymer 1) as the sole binder and Mil-100 (Fe) had a particle size of 82 m 2 In addition, the pellets prepared with water only without any binder maintained the pellet shape after drying, but had a very low crushing strength of 2.4 N and a SSA of 1251 m / s. 2 / g of SSA.
[0151] The experiments further showed that high normalized functionality ratios (NFRs) can be obtained using a combination of polymer 1 and polymer 2 in a specific weight % ratio and the total amount of polymer binder.
[0152] Comparison of polymer binder combinations
[0153] Pellets of a binder combination of Rhoplex GL618 and NaCMC as described above were prepared, but using a different type of polymer combination, wherein the total amount of polymer binder was 10 wt% and the weight percent ratio was 1:1.
[0154] The following polymer binder combinations were tested: 1) Zusoplast PS1 (water soluble) and polyethylene oxide (water insoluble at 25°C); 2) NaCMC (water soluble) and polyethyleneimine (water soluble); and 3) Rhoplex GL618 (water insoluble) and Maincote 5045 (water insoluble).
[0155] It was observed that the pellets prepared with the comparative binder combination had low SSA or poor crush strength compared to the pellets comprising the binder combination Rhoplex GL618 / NaCMC.
[0156] In the foregoing description, concepts have been described with reference to specific embodiments. However, it will be appreciated by those skilled in the art that various modifications and changes may be made without departing from the scope of the invention as set forth in the claims below. Therefore, the description and drawings should be regarded as illustrative rather than restrictive, and all such modifications are intended to be included within the scope of the invention.
Claims
1. A monolithic body comprising a metal organic framework (MOF) and a polymer binder, wherein The polymer binder comprises a first polymer and a second polymer, the first polymer being water-insoluble, having a solubility in water of no greater than 5 g / L water at 25° C., and the second polymer being water-soluble, having a solubility in water of at least 10 g / L water at 25° C.; The amount of the polymer binder is at least 3 wt % based on the total weight of the MOF and the polymer binder; and The monolithic body has an average crush strength of at least 10N.
2. The monolithic body of claim 1, wherein the monolithic body has a specific surface area (SSA) of at least 850 m 2 / g.
3. The monolithic body according to claim 1 or 2, wherein the weight % ratio of the MOF to the polymer binder in the monolithic body is at least 5:
1.
4. The monolithic body according to claim 1 or 2, wherein the amount of the polymer binder is at least 3.0 wt% and not more than 20 wt% based on the total weight of the polymer binder and the MOF.
5. The monolithic body according to claim 1 or 2, wherein the crush strength of the monolithic body is at least 25N.
6. The monolithic body according to claim 1 or 2, wherein the first polymer comprises functional groups and the second polymer comprises functional groups, and the functional groups of the first polymer are capable of forming covalent bonds with the functional groups of the second polymer.
7. The monolithic body of claim 1 or 2, wherein the first polymer comprises at least one polyacrylate, polystyrene, epoxide polymer, polyurethane, polyester, polyether, polyamide, polyimide, or any combination or copolymer thereof.
8. The monolithic body of claim 7, wherein the first polymer comprises a polyacrylate comprising amine functional groups.
9. The monolithic body according to claim 1 or 2, wherein the second polymer comprises a polysaccharide, polyethylene glycol, polyamide, polyvinyl alcohol or polyacrylate.
10. The monolithic body according to claim 9, wherein the second polymer comprises a polysaccharide selected from a cellulose derivative or a starch derivative, an alginate or an alginate derivative.
11. The monolithic body of claim 10, wherein the polysaccharide comprises a salt of carboxymethylcellulose.
12. The monolithic body according to claim 1 or 2, wherein the polymer binder comprises at least partially cross-linked polymers of Polymer 1 and Polymer 2.
13. The monolithic body of claim 12, wherein the first polymer comprises a polyacrylate comprising amine functional groups and the second polymer comprises a salt of carboxymethyl cellulose.
14. The monolithic body according to claim 1 or 2, wherein the polymer binder is permeable to an analyte capable of being adsorbed by the MOF, wherein the analyte is selected from the group consisting of water, carbon dioxide, hydrogen, methane, ammonia, water pollutants, or air pollutants.
15. The monolithic body according to claim 1 or 2, wherein the density of the monolithic body is at least 1.5 g / cm 3 .
